Saltatory conduction in unmyelinated axons: clustering of Na+ channels on lipid rafts enables micro-saltatory conduction in C-fibers - Neishabouri, Ali; Faisal, A. Aldo (Frontiers in Neuroanatomy, 2014)
The action potential (AP), the fundamental signal of the nervous system, is carried by two types of axons: unmyelinated and myelinated fibers. In the former the action potential propagates continuously along the axon as established in large-diameter fibers. In the latter axons the AP jumps along the Nodes of Ranvier – discrete, anatomically specialized regions which contain very high densities of sodium ion (Na + ) channels. Therefore saltatory conduction is thought as the hallmark of myelinated axons, which enables faster and more reliable propagation of signals than in unmyelinated axons of same outer diameter. Recent molecular anatomy showed that in C-fibers, the very thin (0.1 μm diameter) axons of the peripheral nervous system, Nav1.8 channels are clustered together on lipid rafts that float in the cell membrane. This localized concentration of Na+ channels resembles in structure the ion channel organization at the Nodes of Ranvier, yet it is currently unknown whether this translates into equivalent phenomenon of saltatory conduction or related-functional benefits and efficiencies. Therefore, we modeled biophysically realistic unmyelinated axons with both conventional and lipid-raft based organization of Na+ channels. We find that action potentials are reliably conducted in a micro-saltatory fashion along lipid rafts. Comparing APs in unmyelinated fibers with and without lipid rafts did not reveal any significant difference in either the metabolic cost or AP propagation velocity. By investigating the efficiency of AP propagation over Nav1.8 channels, we find however that the specific inactivation properties of these channels significantly increase the metabolic cost of signaling in C-fibers.